The relationship between salivary cortisol and perinatal depression in women undergoing termination of pregnancy for fetal anomaly: A prospective cohort study. (August 2019) - Li, Jinxiu; Tang, Siyuan; Liu, Minhui; Liu, Wei; Cheng, Chunxia; Li, Ying; Sun, Mei; Qin, Chunxiang
Abstract: Background: The hypothalamic-pituitary-adrenal axis plays a crucial role in the neurobiological pathways for depression. The aim of this study was to determine the relationship between salivary cortisol and depression in women before and after termination of pregnancy due to fetal anomaly. Study design: A prospective cohort study was conducted. One-way ANOVA and linear correlation were conducted to analyse the relationship between salivary cortisol and depression before and after termination of pregnancy. Results: No significant difference in morning and evening cortisol levels between women underwent TOP for fetal anomaly without depression and those with depression, but the women underwent TOP for fetal anomaly had significantly higher levels of morning and evening cortisol than women with healthy pregnancy. Cortisol awakening response was lower in women underwent termination of pregnancy, than in women with normal pregnancy; lower in women underwent termination of pregnancy with depression than in those women without depression. Cortisol awakening response also had a negative correlation with depression, and the correlation coefficients for cortisol awakening response and depression after TOP ( R  = 0.461) were higher than the correlation coefficients for cortisol awakening response and depression before TOP( R  = 0.238). Conclusions: Our results were not only useful to support the hypothesis that hypothalamic-pituitary-adrenal axis functioning would turn hypoactive, with depression progressing to increase in severity, but also helpful with insights into the predictive effects of cortisol awakening response in depression after TOP. We suggest that further research should be conducted on the relationship between salivary cortisol and depression before and after TOP for fetal anomaly.